Anion recognition by cyclic peptides. Issue 24 (25th March 2015) - Elmes, Robert B. P.; Jolliffe, Katrina A.
<x xml:space="preserve">Abstract</x> Cyclic peptides provide excellent scaffolds for anion recognition and improved binding affinity and selectivity has been achieved through peptide backbone rigidification and the introduction of side chains bearing anion recognition groups.